2015
DOI: 10.1111/jce.12772
|View full text |Cite
|
Sign up to set email alerts
|

Atrioventricular Nodal Reentrant Tachycardia in Implantable Cardioverter Defibrillators: Diagnosis and Troubleshooting

Abstract: Inappropriate therapies are frequent in patients with implantable cardioverter defibrillators (ICDs) and are associated with adverse outcomes, including increased mortality. Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common reentrant supraventricular tachycardia (SVT) and a cause of inappropriate therapies in these patients. In the present article we review the problem of AVNRT in ICD patients with a focus on diagnosis and the available algorithms to improve arrhythmia discrimination and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Inappropriate therapies are frequent in patients with ICDs and are associated with adverse outcomes, including increased mortality. Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common reentrant narrow complex tachycardia (NCT) and a cause of inappropriate therapies in these patients 1–3 . The differential diagnosis of NCT with ventriculoatrial (VA) dissociation or variable block to the atrium includes junctional ectopic tachycardia (JET), AVNRT with a block in the upper (proximal) common pathway (UCP), orthodromic nodofascicular (NF)/nodoventricular (NV) re‐entry, and a focal tachycardia from the proximal or distal His–Purkinje system (HPS) 4–10 …”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate therapies are frequent in patients with ICDs and are associated with adverse outcomes, including increased mortality. Atrioventricular nodal reentrant tachycardia (AVNRT) is the most common reentrant narrow complex tachycardia (NCT) and a cause of inappropriate therapies in these patients 1–3 . The differential diagnosis of NCT with ventriculoatrial (VA) dissociation or variable block to the atrium includes junctional ectopic tachycardia (JET), AVNRT with a block in the upper (proximal) common pathway (UCP), orthodromic nodofascicular (NF)/nodoventricular (NV) re‐entry, and a focal tachycardia from the proximal or distal His–Purkinje system (HPS) 4–10 …”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be to inactivate the dual-chamber detection criteria (and rely on the morphology criterion to diagnose SVT, assuming that there is no aberrancy). Excellent reviews of ICD troubleshooting in the setting of AVNRT have been published [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] Recently, the multi-centre PRAETORIAN trial reported that in patients without a pacing indication, an S-ICD was non-inferior to the transvenous ICD with respect to device-related complications and inappropriate shock, with no difference in appropriate shock between the two arms. [ 28 ]…”
Section: Rhythm Discrimination In the Subcutaneous Icdmentioning
confidence: 99%